A Global Survey of Self-Reported Cancer Screening Practices by Health Professionals for Kidney Transplant Candidates and Recipients - Nida Saleem; Nida Saleem; Nida Saleem; Wai H. Lim; Wai H. Lim; Jacqueline H. Stephens; Jacqueline H. Stephens; Annabelle Wilson; Billie Bonevski; Allison Jaure; Allison Jaure; Armando Teixeira-Pinto; et al. (Transplant International)
Cancer is a major cause of morbidity and mortality in kidney transplant recipients. Health professionals have a critical role in promoting cancer screening participation. From March 2023 to February 2024, an online survey was distributed to kidney transplant health professionals globally to assess their screening practices. We compared their reported screening practices to recommended guidelines and analyzed factors associated with these practices. We received 97 responses, and most were nephrologists (70%), and around 80% recommended breast, colorectal, and cervical cancer screening for kidney transplant candidates and recipients. About 85% recommended lung cancer screening for higher-risk individuals. Skin cancer screening recommendations varied from 69% for transplant candidates and 84% for recipients. Self-reported cervical cancer screening practices were most concordant with recommended guidelines, followed by breast and skin cancers. Barriers reported included a lack of cancer screening awareness (28%), perceived financial constraints (35%), and deficient structured cancer screening systems (51%). Professionals from high-income countries were more likely to advise screening than those from lower-middle-income countries, with odds ratios ranging from 2.9 to 12.3. Most health professionals reported recommending cancer screening for kidney transplant candidates and recipients. However, recommendations were influenced by costs and service delivery gaps within health systems.